The profit of peace : corporate responsibility in conflict regions - Bais, Karolien, 1951- (Greenleaf, 2005)
It may seem a strange notion to give the private sector a role in conflict prevention or resolution, but multinational corporations (MNCs) do have some characteristics that make them good partners in a well-designed strategy for peace and stability. By focusing on their core competencies, their presence in a conflict region can help to provide prosperity for rebuilding society and its institutions, and improved respect for human rights. This book is not a song of praise for MNCs in general. There is a litany of examples of companies that feel no shame in profiting from conflicts by trading weapons or illegal resources. Instead, this book is about corporations that are disposed to ethical, responsible entrepreneurship: companies that balance their desire for profit with compliance with international business and human rights standards and with a genuine investment in local workers, environmental protection, social development and stability.